Development of Nearpod Learning Media with Deep Learning Methods in Pencak Silat Courses - Surimeirian, M. Anas; Roberto, Julio; Fajar, Muhammad Maulana (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to find out the development of Nearpod using the Deep Learning method in the pencak silat course. Knowing the feasibility of this learning media is based on the assessment of material experts, media experts and students. This type of research and development uses the ADDIE development model developed through five stages, namely Analysis, Design, Development, Implementation and Evaluation. At the Development stage, learning media using Nearpod is assessed for eligibility by material experts and media experts. The implementation stage goes through two stages, namely small group trials and field trials. The results of the study showed that the learning media using Nearpod the feasibility level of this learning media based on the assessment of material experts obtained an average of 4.80 which was included in the very feasible category, media experts obtained an average of 4.80 which was included in the very feasible category, and student assessment, obtained an average overall score of 4.89 which was included in the very feasible category. Based on the results of the research, the learning media developed is very feasible to be used as a learning medium in the Physical Education Study Program to improve straight kick skills in pencak silat courses.